Significant Need for a French Network of Expert Centers Enabling a Better Characterization and Management of Treatment-Resistant Depression (Fondation FondaMental) - Yrondi, Antoine; Bennabi, Djamila; Haffen, Emmanuel; Garnier, Marion; Bellivier, Frank; Bourgerol, Thierry; Camus, Vincent; D’Amato, Thierry; Doumy, Olivier; Haesebaert, Frédéric; Holtzmann, Jérôme; Lançon, Christophe; et al. (Frontiers in Psychiatry, 2017)
Background: Major depression is characterized by i) a high lifetime prevalence of 16-17% in the general population; ii) a high frequency of treatment resistance in around 20-30% of cases; iii) a recurrent or chronic course; iv) a negative impact on the general functioning and quality of life; v) high level of comorbidity with various psychiatric and non-psychiatric disorders, high occurrence of completed suicide, significant burden along with the personal, societal and economic costs. In this context, there is an important need for the development of a network of expert centres for treatment-resistant depression (TRD), as performed under the leadership of the Foundation FondaMental. Methods: The principal mission of this national network is to establish a genuine prevention, screening and diagnosis policy for TRD to offer a systematic, comprehensive, longitudinal, and multi-dimensional evaluation of cases. A shared electronic medical file is used referring to a common exhaustive and standardized set of assessment tools exploring psychiatric, non-psychiatric, metabolic, biological and cognitive dimensions of TRD. This is paralleled by a medico-economic evaluation to examine the global economic burden of the disease and related healthcare resource utilization. Additionally, an integrated biobank has been built by the collection of serum and DNA samples for the measurement of several biomarkers that could further be associated with the treatment resistance in the recruited depressed patients. A French observational long-term follow-up cohort study is currently in progress enabling the extensive assessment of resistant depressed patients. In those unresponsive cases, each expert centre proposes relevant therapeutic options that are classically aligned to the international guidelines referring to recognized scientific societies. Discussion: This approach is expected to improve the overall clinical assessments and to provide evidence-based information to those clinicians most closely involved in the management of TRD thereby facilitating treatment decisions and choice in everyday clinical practice. This could contribute to a significant improvement in the often poor prognosis, the relapsing course, daily functioning and heavy burden of TRD. Moreover, the newly created French network of expert centres for TRD will be particularly helpful for a better characterization of socio-demographic, clinical, neuropsychological and biological markers of treatment resistance required